Analysis of Factors Affecting Community View on Covid-19 Vaccination - Salmiani abdul manaf; Irnawati (Institute of Computer Science (IOCS), 2022)
Indonesia is a country of law and has issued policies related to vaccination during the covid-19 pandemic, as in the Regulation of the Minister of Health Number 84 of 2020 (Concerning the 2019 War Against Corona Virus Disease (Covid-19) in the context of implementing vaccinations) as described in) pandemic.Judging from the prevalence of Covid-19 cases, the current need is to develop a safe and effective COVID-19 vaccine that can trigger an appropriate immune response to stop the COVID-19 pandemic. Objective: The purpose of this Systematic Review is to analyze the influence of public opinion on the covid-19 vaccination. Methods: Database searches include Google Scholar, Science Direct, and Pubmed with keywords. The keywords used are views, perceptions, covid 19 vaccination, Implementation of Covid-19 Vaccination, Vaccine Effectiveness. The next stage is to select articles according to the criteria, which are published in 2019-2022 with the full text of 13 articles that meet the inclusion criteria. Showing public doubts about the covid 19 vaccination, which was reinforced by the slanted news about the vaccine, some said they died, or got the virus again. So it can be said that people do not understand the use of the vaccine itself. That's. It is hoped that the government's duty is to continue to encourage and campaign about vaccination, because this way we can break the chain of virus spread. The public is asked to be patient in going through this pandemic, because it is not only Indonesia, but the whole world.